Learning-adjusted years of schooling (LAYS): Defining a new macro measure of education. (August 2020) - Filmer, Deon; Rogers, Halsey; Angrist, Noam; Sabarwal, Shwetlena
Abstract: The standard summary metric of education-based human capital used in macro analyses is a quantity-based one: The average number of years of schooling in a population. But as recent research shows, students in different countries who have completed the same number of years of school often have vastly different learning outcomes. We therefore propose a new summary measure, the Learning-Adjusted Years of Schooling ( LAYS ). This measure combines quantity and quality of schooling into a single easy-to-understand metric of progress, revealing considerably larger cross-country education gaps than the standard metric. We show that the comparisons produced by this measure are robust to different ways of adjusting for learning and that LAYS is consistent with other evidence, including other approaches to quality adjustment. Like other learning measures, LAYS reflects learning, and barriers to learning, both inside and outside of school; also, cross-country comparability of LAYS rests on assumptions related to learning trajectories and the validity, reliability, and comparability of test data. Acknowledging these limitations, we argue that LAYS nonetheless improves on the standard metric in key ways.